Data for: Hermetic bags minimize postharvest loss during at least four successive cycles of storage in Mexican highlands - Odjo, Sylvanus; Verhulst, Nele (International Maize and Wheat Improvement Center, 2024)
CIMMYT implemented a study at its station in Texcoco to compare the effectiveness of 5 different storage technologies in minimizing grain loss during four consecutive storage cycles. In each storage cycle, the conventional practice of farmers in the area, polypropylene bag, was compared to four hermetic plastic bags from three different brands ((1) GrainPro® Hermetic Bag Premium TM Zipper (HBZ), (2) GrainPro® Hermetic Bag Premium TM Twist & Tie (HBT), (3) Ecotact 80 Multilayered Hermetic Storage Bag (HEC), (4) ZeroFly® Hermetic Storage Bag (ZFLY)) and silage plastic bag (an alternative low-cost plastic bag used as hermetic technology). The same experiment was repeated during four cycles to evaluate how each technology maintains its performance in minimizing storage loss. After the first storage cycle, the number of holes in each bag due to insect activities was counted. The data collected during each storage cycle included (1) characteristics of the storage cycle, including the crop and variety evaluated; (2) storage technologies evaluated; (3) grain damage, percentage of insect-damaged grain and weight loss; (4) the number of holes per bag. (2024-09-22)